Effects of family socioeconomic status on the self-expectations of children under grandparenting in China - QiXuan Hu (Frontiers in Public Health)
IntroductionThe increasing expansion of grandparenting necessitates further study of the effects of grandparenting on child development. This study investigated the relationship between family socioeconomic status (SES) and children’s self-expectations in households involving grandparenting, using data from the “China Family Panel Studies” (CFPS). The CFPS is a national, large-scale, multidisciplinary social tracking survey conducted by the Institute of Social Science Survey (ISSS) at Peking University.MethodsThe analysis drew on data from 4,946 children aged 6-16 and their families, collected from CFPS2016 to CFPS2018. To determine whether grandparenting was involved, responses from the Children’s parents’ questionnaire were used. Any caregiving arrangement involving grandparents-whether during the day, at night, or both-was classified as grandparenting. Correlational and hierarchical regression analyses were conducted to examine the association between family SES and children’s self-expectations.ResultsThe findings revealed a significant negative correlation between family SES and children’s self-expectations, including its various dimensions, in both groups of families. Additionally, family SES was found to negatively predict children’s self-expectations. A potential explanation for this result is that children from low-income families may have a stronger desire to improve their environmental and social circumstances, fostering greater internal motivation and higher self-expectations. In comparison to families without grandparenting, those with grandparenting had significantly lower family SES, children’s self-expectations, parent-child communication, and parental marital status, with more students studying in non-elite schools. Parent-child communication and residential areas for children can positively predict children’s self-expectations in both groups of families.DiscussionThese findings highlight the significance of family SES and the influence of multiple factors for raising the self-expectations of children under grandparenting. Thus, to improve the quality of life for children under grandparent care and promote their physical and mental health requires a multi-level approach involving the state, society, and individuals within the family.